Identification and characterization of cow's milk proteins from the rat intestinal lymph using a proteomic strategy. Issue 17 (7th August 2013) - Li, Xundou; Wei, Lilong; Jia, Lulu; Li, Menglin; Zhu, Lisi; Liu, Liu; Gao, Youhe
<x xml:space="preserve">Abstract</x> Food proteins were considered to be absorbed into the body after being digested to amino acids, dipeptides, and tripeptides. However, there are studies indicating that some proteins can pass through the intestinal epithelium under normal physiological conditions, perhaps not in sufficient quantities to be of nutritional importance, but in quantities that may be antigenically or biologically active. In the present study, rat intestinal lymph samples were collected using a modified lymph fistula rat model in fasting and cow's milk postprandial states. Low molecular weight proteins were enriched by ultrafiltration and differential solubilization, separated by 1D‐SDS‐PAGE, digested in‐gel based on molecular weight, and identified using nano‐LC‐MS/MS. In the postprandial rat intestinal lymph, nine bovine‐specific proteins (false discovery rate ≤1%) were identified in different molecular weight regions. Most proteins identified in lymph were highly abundant proteins in the milk, such as β‐lactoglobulin and caseins. Seven of the nine identified bovine‐specific proteins are allergens in milk. This strategy can be used to search for proteins that can enter the intestinal lymph and analyze their common features. Understanding the common features of these proteins might help to develop protein drugs taken orally, so that therapeutic proteins might embody fusion domains for cross‐barrier transport or translocation.